Effect of Tween 20 on antibacterial effects of acidic, neutral and alkaline decontaminants on viability of Salmonella on chicken carcasses and survival in waste decontamination fluids - Dikici, Abdullah; Arslan, Ali; Yalcin, Halil; Ozdemir, Pinar; Aydin, Isil; Calicioglu, Mehmet (Elsevier Sci Ltd, 2013)
The effect of Tween 20 on antimicrobial effects of acidic (lactic acid), neutral (cetyl pyridinium chloride) and alkaline (trisodium phosphate) decontaminants to reduce the numbers of Salmonella inoculated to broiler carcasses were studied. In addition, survival of Salmonella in waste decontamination fluids was investigated. For this purpose, an average of 7 +/- 1 log(10) cfu/ml Salmonella Enteritidis and Salmonella Typhimurium cocktail was surface-inoculated on to a total of 110 broiler carcasses. Contaminated carcasses were immersed in to tap water (control), lactic acid (LA) (1-2%), cetyl pyridinium chloride (CPC) (0.5-1%), or trisodium phosphate (TSP) (8%) and the combinations of these treatments with Tween 20 (TW20) (0.5%) for 15 min. Results indicated that. Salmonella numbers significantly decreased (P < 0.05) in all groups, except control and 1% LA. No significant difference was found between treatments with and without TW20. In waste decontamination fluids, 6.68 and 3.41 log(10) cfu/ml of Salmonella were recovered from control and CPC groups, respectively, while no viable Salmonella cell was detected in LA and TSP groups by direct plating. It was concluded that regardless of TW20, the antimicrobials tested were effective to reduce Salmonella in poultry carcasses. However, the pathogen may survive in neutral waste decontamination fluid such as CPC and can pose a risk for consumer health by contaminating the plant environment. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Salmonella; Broiler; Decontamination; Waste decontamination fluids; Tween 20